Phased thermodynamic reduction rate model of continuous magnesium smelting process - Jing-zhong Xu; Ting-an Zhang; Hong-xuan Liu (Journal of Magnesium and Alloys)
Compared with vacuum continuous magnesium smelting process, it has important advantages of significantly lower energy consumption and carbon emissions, which makes it possible to realize green magnesium smelting. In the process of industrialization, the reduction efficiency of prefabricated pellets affects both the yield of metallic magnesium and the utilization efficiency of reducing slag. In this paper, the pore-forming agent was added to the prefabricated pellets, and the mechanism of different pore-forming stages was analyzed by micro-nano simulation. The results show that the dehydration pore-forming stage has the greatest influence on the reduction rate of pellets. A theoretical model of the relationship between porosity and reduction efficiency of prefabricated pellets in a relatively vacuum atmosphere was established, which was well verified by dehydration pore-forming stage, calcination pore-forming stage and reduction pore-forming stage. It is verified by experiments that the reduction efficiency of prefabricated pellets can be increased from 91.42% to 99.93% after adding pore-forming agent.